A Study On Students’ Perception Of Reading Strategies While Comprehending An Academic Text By UTM Students - Abdul Razak, Noor Zainab; Amir, Siti Norashikin (2010)
Reading is a skill that enables readers to acquire knowledge and information from the text that they have read. The use of adequate reading strategies while reading can help the readers be independent and efficient readers. Therefore, the aim of this research is to identify the perception of first year students of Universiti Teknologi Malaysia, Skudai towards the reading strategies while comprehending an academic text. The respondents of this research are first year students who are taking UHB 1412 (English for Academic Communication) course from various faculties in UTM for the 2008/2009 session which consists of 60 students. A set of questionnaire containing 58 items were distributed to the respondents to analyse the reading strategies used by them. The analysis was carried out to find the frequency, percentage and mean. Based on this research, it was found that the students use the three reading strategies as proposed which are cognitive, metacognitive and social reading strategies while comprehending the text that they read. Besides that, it was found that the social reading strategy is the most frequently used by the first year students. However, based on the result found, there are not many differences in the number and type of strategies used by the high and low proficiency students. Based on the analysis, the high proficiency students use all three reading strategies proposed by the researcher while for the low proficiency students, all of them use metacognitive reading strategies but not the other two strategies. Discussions on recommendations for further research have been made as reference for other researchers who are interested in carrying out researches in this field.